Customer Satisfaction and Stock Returns Risk - TULI, Kapil R. (Institutional Knowledge at Singapore Management University, 2009)
Over the past decade, several studies have argued that customer satisfaction has high relevance for financial markets because it has a significant impact on stock returns. However, little attention has been given to understanding the impact of customer satisfaction on the risk of stock returns. The finance literature suggests that investors that judge performance only in terms of returns place more resources than warranted in risky opportunities, forgo profitable opportunities, and apply misguided performance evaluations. Accordingly, this study develops, tests, and finds empirical support for the hypotheses that positive changes (i.e., improvement) in customer satisfaction result in negative changes (i.e., reduction) in overall and downside systematic and idiosyncratic risk. Using a panel data sample of publicly traded U.S. firms and satisfaction data from the American Customer Satisfaction Index, the study demonstrates that investments in customer satisfaction insulate a firm's stock returns from market movements (overall and downside systematic risk) and lower the volatility of its stock returns (overall and downside idiosyncratic risk). The results are robust to alternative measures of risk, model specifications, and concerns related to sample composition criteria raised in some recent studies. Therefore, the results indicate that customer satisfaction is a metric that provides valuable information to financial markets. The robust impact of customer satisfaction on stock returns risk indicates that it would be useful for firms to disclose their customer satisfaction scores in their annual report to shareholders.